Inovasi Pengolahan limbah Sabut Kelapa Menjadi Pupuk Cair Organik Sebagai Upaya Pemberdayaan Masyarakat Desa Candiwatu - Nurrochmah, Aliatus; Nur Fitroten Dian Sari; Bramantyo, Danendra; Sri Diyanti, Daffa Dwi (Bhumiputra: Jurnal Penelitian dan Pengabdian Masyarakat Global, 2025)
Candiwatu Village has significant potential for coconut plantations, but the coconut husk waste produced so far has not been optimally utilized. The accumulation of waste often causes environmental problems, even though coconut husks have high lignin and cellulose content, making them suitable for processing into economically valuable organic liquid fertilizer. This community service activity aims to empower residents through education and hands-on practice in processing coconut husk waste into organic liquid fertilizer. The implementation method involves preparation, execution, and evaluation stages using a service-learning approach. The target audience includes women's study groups, members of coconut-processing SMEs, and the Youth Association. The results of the activity showed high community participation, with an attendance rate of 92% and an understanding of fermentation techniques at 88%. On average, each household successfully processed approximately 3 kg of coconut husks into 5 liters of liquid fertilizer over a 14-day fermentation period. The use of organic liquid fertilizer in home gardens had a positive impact, with an average increase in plant growth of 15%. This program not only reduces organic waste but also encourages the formation of community workgroups committed to continuing fertilizer production independently. This activity is expected to serve as a model for sustainable community empowerment in rural areas.